Meigs’ syndrome: how we mistook the diagnosis in a tertiary oncology centre in India; an opinion piece on the surgeon’s responsibility in minimizing the stress of the cancer patient and family - Ray, M. D.; Josephin, J. R. Jeena; Kapila, Shivani; N., Premanand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Typical Meigs syndrome may mislead the surgeon as advanced ovarian cancer. CECT can identify the huge ovarian mass, ascites and pleural effusion. Mostly Surgeon’s mind focuses towards the pleural effusion with elevated CA 125 as stage IVa ovarian cancer because of the rarity of this syndrome. But it is Surgeon’s responsibility to diagnosis of Meigs syndrome beforehand to alleviate the pain of the patient and her family. Meigs’ syndrome typically presents with the triad of an ovarian mass, ascites and pleural effusion. The latter two resolved after removal of the mass. As this syndrome is a rare entity, this presentation of an ovarian mass may mislead the surgeon, biasing his or her mind towards advanced ovarian malignancy. Along with these if the CA-125 is also raised, the patient is usually labelled as stage IVa ovarian cancer, causing immense distress to the patient and family. This makes it even more imperative that the surgeon diagnoses this syndrome beforehand to avoid the pain of the patient and family.